1998
DOI: 10.1007/s002470050401
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous gastrostomy tube placement in patients with ventriculoperitoneal shunts

Abstract: Our study indicates children with ventriculoperitoneal shunts who undergo percutaneous gastrostomy are at greater risk for infection and subsequent shunt malfunction. Therefore, we recommend prophylactic antibiotic therapy to cover for skin and oral flora.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 3 publications
1
22
1
Order By: Relevance
“…Other studies, including those published by Baird et al and Graham et al demonstrated no shunt infections [4,5]. Shunt infection occurred in a total of seven patients (12.7%) in our study, similar to the 9% incidence of shunt infection noted in a study of PEG tube placement in children with VP shunts by Sane et al [7]. This rate of infection is similar to that reported in published literature for VP shunts in patients without PEG tube placement, which has ranged from 3 to 29% [8,[12][13][14][15].…”
Section: Infectionsupporting
confidence: 90%
See 1 more Smart Citation
“…Other studies, including those published by Baird et al and Graham et al demonstrated no shunt infections [4,5]. Shunt infection occurred in a total of seven patients (12.7%) in our study, similar to the 9% incidence of shunt infection noted in a study of PEG tube placement in children with VP shunts by Sane et al [7]. This rate of infection is similar to that reported in published literature for VP shunts in patients without PEG tube placement, which has ranged from 3 to 29% [8,[12][13][14][15].…”
Section: Infectionsupporting
confidence: 90%
“…Indeed, review of the literature reveals four studies reporting experience with this combination of procedures. However, the four completed studies encompass a total of only 60 patients [4][5][6][7]. As such, percutaneous G-tube placment, VP shunt prior to G-tube, or G-tube prior to VP shunt or in shunt infection rates within the first year after placement several questions regarding the placement of PEG tubes in patients with VP shunts persist.…”
Section: Discussionmentioning
confidence: 94%
“…Sane et al [14] reported a 9% incidence of peritonitis and subsequent VP shunt infection with CSF cultures positive for Streptococcus viridans and S. aureus. However, there were no prophylactic antibiotics given prior to the procedure and all PEGs were inserted by the antegrade technique.…”
Section: Discussionmentioning
confidence: 99%
“…The infective complications of PEG include stoma site infection in 3-9% and peritonitis in 1-7% [9]. The standard pull-through technique of PEG insertion exposes the gastrostomy tube to oropharyngeal bacterial flora.…”
Section: Discussionmentioning
confidence: 99%